The clinical utility of polygenic risk scores in genomic medicine practices: a systematic review - Judit Kumuthini; Brittany Zick; Angeliki Balasopoulou; Constantina Chalikiopoulou; Collet Dandara; Ghada El-Kamah; Laura Findley; Theodora Katsila; Rongling Li; Ebner Bon Maceda; Henrietta Monye; Gabriel Rada; et al. (Human Genetics, 2022)
Genomic medicine aims to improve health using the individual genomic data of people to inform care. While clinical utility of genomic medicine in many monogenic, Mendelian disorders is amply demonstrated, clinical utility is less evident in polygenic traits, e.g., coronary artery disease or breast cancer. Polygenic risk scores (PRS) are subsets of individual genotypes designed to capture heritability of common traits, and hence to allow the stratification of risk of the trait in a population. We systematically reviewed the PubMed database for unequivocal evidence of clinical utility of polygenic risk scores, using stringent inclusion and exclusion criteria. While we identified studies demonstrating clinical validity in conditions where medical intervention based on a PRS is likely to benefit patient outcome, we did not identify a single study demonstrating unequivocally such a benefit, i.e. clinical utility. We conclude that while the routine use of PRSs hold great promise, translational research is still needed before they should enter mainstream clinical practice.